Survey of Schistosoma haematobium and Environmental Factors in Donga Local Government Area, Taraba State, Nigeria - J, Agbo O.; Tatah, Silas; M, Dawuda B. (International Journal of Humanities, Education, and Social Sciences, 2024)
Schistosoma haematobium infection is known to be endemic especially among residents along Rivers, This study was conducted to establish the preval_ence of urinary schistosomiasis in relation to some epidemiological factors among elementary pupils in Donga Local Government Area. Urine filtration technique using polycarbonate membrane filters was employed to check the presence of Schistosoma haematobium eggs in urine and questionnaires were administered. Overall preval_ence of 8.94% (21) was recorded out of the 235 urine examined. Chi square analysis showed insignificant association of the infection with the various schools (χ²= 6.192, P = 0.185). Similarly, ANOVA revealed no significant difference in the mean egg intensity (27.29 eggs/10ml of urine) among the schools (p = 0.293). Males were more infected 13.33%(16) than females 4.50%(5) with a significant difference (P=0.020). However, there was no statistical significant difference in their mean egg intensities (30.3 eggs/10ml of urine in male and 17.6 eggs/10ml of urine in female) (p = 0.27). The age-related preval_ence was higher 11.82% (13) in 10-15 years children while children aged 16-20 had the least preval_ence 0.01% (1). Chi square showed statistical significant association between infection and age (χ²=12.964, P=0.002). But there was a statistical insignificant difference between their mean egg intensities; 10-15, 4-9 and 16-20 (31.08, 23.4, 5 eggs/10ml of urine respectively) with p=0.462. Children who fish had the highest preval_ence 16.67% and children that do not partake in any of these activities had no case of infection 0%(64). Chi square revealed a statistical significant association between participant's water contact activities and infection (χ² =11.21; p = 0.024). However, ANOVA showed statistical insignificant difference in the mean egg intensity among these activities (p = 0.486). This findings indicates that urinary schistosomiasis has low endemicity in this area which could be due to the fact that It was concluded that the overall low preval_ence could be attributed to improved environmental hygiene among others.